2002
DOI: 10.1080/00014788.2002.9728966
|View full text |Cite
|
Sign up to set email alerts
|

Auditor economic incentives and going-concern opinions in a limited litigious Continental European business environment: empirical evidence from Belgium

Abstract: Abstract-Theory predicts that auditor reporting behaviour may be influenced by the perceived consequences of disclosing going-concern uncertainty in the audit report (DeAngelo 1981, Watts andZimmerman 1986). Krishnan and Krishnan (1996) and Louwers (1998) have addressed this issue empirically in a US context. The results of Krishnan and Krishnan (1996) suggested that one of the important factors in the auditor's opinion decision is the risk of litigation. The purpose of this study is to examine the relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 28 publications
7
38
1
3
Order By: Relevance
“…A similar conclusion was reached by Vanstraelen (2002) who investigated the Belgian audit market. Nevertheless, Vanstraelen's (2002) methodological approach was different from the former, because its sample was formed by bankrupt companies, financially stressed non-bankrupt companies and financially non-stressed non-bankrupt companies, all three categories with the same weight. Geiger and Raghunadan (2002) defined audit reporting failures as the inability of the auditor to issue a going-concern opinion to a company entering bankruptcy.…”
Section: Audit Tenure and Auditor Independencesupporting
confidence: 59%
See 2 more Smart Citations
“…A similar conclusion was reached by Vanstraelen (2002) who investigated the Belgian audit market. Nevertheless, Vanstraelen's (2002) methodological approach was different from the former, because its sample was formed by bankrupt companies, financially stressed non-bankrupt companies and financially non-stressed non-bankrupt companies, all three categories with the same weight. Geiger and Raghunadan (2002) defined audit reporting failures as the inability of the auditor to issue a going-concern opinion to a company entering bankruptcy.…”
Section: Audit Tenure and Auditor Independencesupporting
confidence: 59%
“…Does a "honeymoon period" exist in the Spanish market? Levinthal and Fichman (1988) and Vanstraelen (2002) observed that the likelihood of qualified opinions increased just after the first years of engagement. The former authors named this effect a honeymoon period in the auditor-client relationship.…”
Section: Some Additional Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Louwers (1998) and Carcello and Neal (2000), with samples of US financially distressed firms, did not find a negative effect of tenure on the auditors' reporting decision. A similar conclusion was reached by Vanstraelen (2002) and Knechel and Vanstraelen (2007) for the Belgian market, and by Ruiz-Barbadillo et al (2004) and for the Spanish market. This evidence supports that the litigation risk faced by the auditor when an unqualified report is issued to a company which deserves an audit report with GCMO would offset the 'familiarity threat' associated to long tenures with the audit firm.…”
Section: Review Of the Literaturesupporting
confidence: 59%
“…For instance, in auditing standard there should be a clear and objective indicator like when Altman z-score of a client is -1 or less, it is compulsory for an auditor to issue GC opinion. Previous researchers suggested that a more objective auditing standard (which can cause less auditor discretion) could lead to a more accurate GC opinion issuance (Vanstraelen, 2000(Vanstraelen, , 2002(Vanstraelen, , 2003.…”
Section: Points To Contemplatementioning
confidence: 99%